2017
DOI: 10.3390/ijms18020295
|View full text |Cite|
|
Sign up to set email alerts
|

Whole Exome Sequencing in Psoriasis Patients Contributes to Studies of Acitretin Treatment Difference

Abstract: Psoriasis vulgaris is an immune-mediated inflammatory skin disease. Although acitretin is a widely used synthetic retinoid for moderate to severe psoriasis, little is known about patients’ genetics in response to this drug. In this study, 179 patients were enrolled in either the discovery set (13 patients) or replication set (166 patients). The discovery set was sequenced by whole exome sequencing and sequential validation was conducted in the replication set by MassArray assays. Four SNPs (single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
12
1
1
Order By: Relevance
“…Pharmacogenetics is a subject to explore the correlation between genetic information and drug response 46‐48 . However, few reports have been focused on the association between gene polymorphisms and MTX efficacy.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Pharmacogenetics is a subject to explore the correlation between genetic information and drug response 46‐48 . However, few reports have been focused on the association between gene polymorphisms and MTX efficacy.…”
Section: Discussioncontrasting
confidence: 42%
“…Pharmacogenetics is a subject to explore the correlation between genetic information and drug response. [46][47][48] However, few reports have been focused on the association between gene polymorphisms and MTX efficacy. Previous studies have shown that ABC transporter family members are associated with MTX efficacy, including polymorphisms in the ABCC1, and ABCG2 genes, and other genetic polymorphisms of RFC-1, 49,50 MTHFR, 51,52 ATIC, 53 FPGS 54 and FOXP3.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found SFRP4 rs1802073 polymorphism was associated with the response to acitretin, namely, the psoriatic patients who carries T allele had a better response than that in G allele carriers ( Zhou et al, 2017 ). SFRP4 rs1802073 polymorphism is a missense mutation (G>T), and induce a proline to change into threonine at position 320 in the SFRP4 protein.…”
Section: Discussionmentioning
confidence: 90%
“…In our previous research, we showed that secreted frizzled-related proteins 4 (SFRP4) rs1802073G>T was a missense mutation and was significantly associated with the response to acitretin ( Zhou et al, 2017 ). SFRP4 is a frizzled decoy receptor that binds to Wnt/β-catenin and inhibits the Wnt/β-catenin signaling pathway, through competing surface receptors ( Carmon & Loose, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…We would like to submit the following correction to the published paper [ 1 ], the reason for this action is that the data in Table 3 were reanalyzed by one more accurate statistic method: On page 12, the sentence of paragraph three “OR and 95% CI were calculated by limited backward-LR (likelihood ratio) logistic regression analysis with adjustment by clinical variables” should be corrected into “OR and 95% CI were calculated by limited enter logistic regression analysis with adjustment by clinical variables”. The corrections resulted some changes in Table 3 and related data in text, while the significance and the conclusions remained unchanged.…”
mentioning
confidence: 99%